Comportamiento de los trabajadores a tiempo parcial desde una perspectiva dinámica: Un análisis para Espa\~na con datos de la Muestra continua de vidas laborales 2005 - Pablo de Pedraza; Rafael Mu\~noz de Bustillo; Luis A. Rivas Herrero (Colegio de Economistas de A Coru\~na, 2008)
– This paper analyzes job transitions for part-time workers in Spain. The first section of the paper reviews existing literature that applies to the Spanish case. First, we selected a sample from the 'continuous sample of work history 2005b' of Spain's Social Security, with individuals who had a part time job in 2001. Then we analyzed their different job paths for the period 2001-2005. The resulting analysis shows 5 categories: individuals that continued working part-time, those who underwent from P/T to F/T jobs, those who ended up in unemployment or inactivity and those individuals who undertook more than a specific number of jobs. Finally, we estimated the probabilities for individuals to fall in any of these categories, by using variables such as sex, age, professional rank and job sector.
Keywords: 330; transiciones laborales; mercado de trabajo; trabajo a tiempo parcial